The chemistry of titanium and related studies - Lucas, C; Lucas, C.R. (1972)
﻿ This thesis describes some studies of mono- and bis(andpi;-cyclopentadienyl)titanium and bis(andpi;-cyclopentadienyl)niobium systems. In Chapter I, publications which are relevant to work discussed later in the text and which have appeared in the literature since 1967 are reviewed. At the end of the chapter, a formal method for the classification of covalent compounds of an element in terms of electron number, valence number, and ligand bond number is described and its usefulness illustrated. In Chapter II, the preparation and some properties of several complexes of trivalent titanium with nitrogen- and phosphorus-donor ligands are described, as well as two new preparations of [(andpi;-C5H5)2TiCl]2 and a preparation of [(andpi;-C5H5)TiCl2]n. The new complexes are of the form: (andpi;-C5H5)2TiClandsdot;L (L = a monodentate ligand), [(andpi;-C5H5)2Tiandsdot;Landprime;2]A (Landprime;2 = a chelating bidentate ligand; A = Cl or PF6), [(andpi;-C5H5)2TiCl]2andsdot;LandPrime;2 (LandPrime;2 = a bridging bidentate ligand), (andpi;-C5H5)2TiCl2andsdot;2L and (andpi;-C5H5)2TiCl2andsdot;Landprime;2. These compounds were characterized by analysis, i.r. and in some cases e.s.r. spectroscopy. In some cases, cryoscopic molecular weight determinations and solution conductivity studies were made. From the occurrence of these compounds, certain conclusions about the electronic and steric environments of andpi;-cyclopentadienyltitanium species are drawn and the implications of these conclusions, concerning the ability of such systems to function as nitrogen fixation catalysts, are discussed. In Chapter III, several attempts to prepare trivalent organo-titanium compounds, (andpi;-C5H5)2TiR or (andpi;-C5H5)TiR2, that contain the metal bonded only to carbon are described. It seems that such compounds are unstable with respect to disproportionation and as a result, certain conclusions are drawn concerning the structure of the compound currently formulated as (andpi;-C5H5)2TiPh. The divalent and tetravalent titanium-containing products of several disproportionation reactions have been examined and the tetravalent ones of general formula (andpi;-C5H5)2TiR2, or (andpi;-C5H5)TiR3 have been identified. A mechanism is proposed for the disproportionation reactions and some studies in support of the proposed mechanism are reported. The reversible fixation of molecular nitrogen by a system similar to that described by Vol'pin and Shilov is also described briefly. As a result of the conclusions reached in Chapter III concerning the instability with respect to disproportionation of trivalent organo-titanium compounds, an attempt was made to obtain information concerning the structure of the stable trivalent titanium compound, (andpi;-C5H5)2Ti(andsigma;-C5H5) This initially involved oxidation of that compound with ferric chloride, silver hexafluorophosphate and silver tetrafluoroborate, in hopes of obtaining the cation [(andpi;-C5H5)2Ti(andsigma;-C5H5)]+. The product of these reactions was, however, (andpi;,-C5H5)2TiX2, X having been derived from the anionic part of the oxidizing agent. The structure of tris(cyclopentadienyl)titanium was therefore determined and a unique type of bonding between the metal and only two carbon atoms of one of the three planar cyclopentadienyl rings was discovered. In Chapter IV, new preparations of (andpi;-C5H5)2NbCl2, (andpi;-C5H5)2NbBH4, and (andpi;-C5H5)2Nb(H)PR3 in high yield are described. The properties of the hydrides as Lewis bases have been examined and as a result, the dihydride cation, [(andpi;-C5H5)2Nb(H)2PMe2Ph]+, has been isolated and characterized. Investigation of phosphine exchange is reported as is the preparation of a highly reactive substance believed to be (andpi;-C5H5)2Nb(CN)TCNE. Exchange of the hydride ligand for a halogen to give (andpi;-C5H5)2Nb(Br)PMe2Ph is reported, as well as the ease with which the phosphine hydrides are oxidized to the corresponding dihalides, (andpi;-C5H5)2NbX2, by substances containing halogen atoms or pseudohalogen functional groups. This property has led to the preparation, inter alia, of (andpi;-C5H5)2NbBr2 and (andpi;-C5H5)2Nb(NCS)2. Finally, brief comparison between niobium, molybdenum, and titanium chemistry relevant to the work in this thesis is made. In Chapter V, details of instrumentation and experimental procedure are given while in the Appendix tables of analytical, molecular weight, conductivity, i.r., and decomposition point data are presented, as well as the preparation and a few reactions of {[andpi;-C6Me6)TiCl2]3}Cl.